Optimization of ultrasound-assisted extraction for antioxidant activity in relation to rhoifolin content of Fortunella polyandra using response surface methodology (RSM) - Hazim Syahmi Elias; Syarul Nataqain Baharum; Kamalrul Azlan Azizan; Wan Yaacob Wan Ahmad; Sheela Chandren; Norazah Basar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Fortunella polyandra (Ridl) Tanaka or Malayan kumquat, is a family of Rutaceae from Malaysia known for its various active compounds, especially flavonoids. This study aims to verify the optimum condition and correlation of leaves extract in Fortunella polyandra by ultrasound-assisted extraction (UAE) for antioxidant activities and apigenin 7-O-neohesperidoside (rhoifolin) contents using the response surface methodology (RSM). Central composite rotatable design (CCD) was performed to investigate the influence of the extraction parameters on maximum antioxidant activity, namely temperatures (X1), times (X2), and solvent ratios of ethanol:water (X3). The optimal extraction conditions for 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity were obtained at extraction time of 5 min, temperature of 30 °C and solvent ratio of 70:30, ethanol:water with IC50 value of 0.126±0.004 mg/mL. Rhoifolin content and ferric reducing antioxidant potential (FRAP) assay share the same optimum condition at extraction time of 5 min, temperature of 30 °C, and solvent ratio of 30:70, ethanol:water. Under these conditions,rhoifolin content was measured at 67.83±0.37 ppm, whereas FRAP equivalent value was recorded at 0.22±0.01 mg/mL. All three responses from the model achieved 95% confidence level. Correlation study showed that there is no relationship between the rhoifolin content and the antioxidant activities of Fortunella polyandra extract.